Pendampingan Akses Pembiayaan dan Kemitraan sebagai Upaya Penguatan BUMDes Tetus Kuanheum, Kabupaten Kupang - Diliana, Widia Octari; Malau, Eve Ida (Universitas Pahlawan Tuanku Tambusai, 2025)
Tetus Kuanheun Village Owned Enterprise faces limited funding and obstacles in establishing strategic partnerships with various parties, resulting in poor business management and development capabilities. This community service activity aims to strengthen financial literacy, increase capital acquisition capabilities, expand partner networks, and sustainably develop the business. The Community Partnership Program is implemented through mentoring methods in the form of outreach and Focus Group Discussions (FGDs). The results of these activities indicate that Village Owned Enterprise administrators have a better understanding of alternative access to formal and informal financing, the importance of collaboration with financial institutions, local governments, the private sector, and digital platforms, and increased awareness of the importance of financial literacy and a strong partnership network. By strengthening financial literacy, Village Owned Enterprise has the potential to increase its competitiveness and contribution to Village Original Income in a sustainable manner.